1999
DOI: 10.1074/jbc.274.31.21499
|View full text |Cite
|
Sign up to set email alerts
|

LEKTI, a Novel 15-Domain Type of Human Serine Proteinase Inhibitor

Abstract: Proteinase inhibitors are important negative regulators of proteinase action in vivo. We have succeeded in isolating two previously unknown polypeptides (HF6478 and HF7665) from human blood filtrate that are parts of a larger precursor protein containing two typical Kazaltype serine proteinase inhibitor motifs. The entire precursor protein, as deduced from the nucleotide sequence of the cloned cDNA, exhibits 15 potential inhibitory domains, including the Kazal-type domains, HF6478, HF7665, and 11 additional si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
196
0
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(206 citation statements)
references
References 24 publications
4
196
0
6
Order By: Relevance
“…As single domains 1, 5, and 6 have been isolated from ultrafiltrates of human blood (10,17) and a 30 kDa LEKTI fragment corresponding to approximately four domains starting with domain 8 was isolated from human epidermal keratinocyte-conditioned media (18), we suggest that both single-and multiple-domain fragments of LEKTI occur naturally.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…As single domains 1, 5, and 6 have been isolated from ultrafiltrates of human blood (10,17) and a 30 kDa LEKTI fragment corresponding to approximately four domains starting with domain 8 was isolated from human epidermal keratinocyte-conditioned media (18), we suggest that both single-and multiple-domain fragments of LEKTI occur naturally.…”
mentioning
confidence: 91%
“…Testing of various serine proteinases showed that domain 6 is an efficient (IC 50 = 150 nM) but temporary inhibitor of trypsin (10). Trypsin inhibitory activity has also been found for natural domain 5 and recombinant domains 8 and 15 (17).…”
mentioning
confidence: 99%
“…SPINK5 is involved in regulation of proteolysis in epithelia formation and keratinocyte terminal differentiation, and some mutations in the SPINK5 gene cause defects in the skin barrier. 8 SPINK5 is expressed in thymus, tonsil and oral mucosa, 10 and it is suggested that abnormal maturation of T lymphocytes in patients with Netherton syndrome alters Th2-type responsiveness to allergens, leading to elevated IgE levels. 8 A recent study of Caucasian AD families showed that maternally derived alleles of the SPINK5 gene are associated with development of atopic diseases such as AD and asthma, suggesting a parent-oforigin effect in the development of atopic diseases.…”
mentioning
confidence: 99%
“…SPINK5 (serin protease inhibitor Kazal-type 5) encodes the Kazal-type serin protease inhibitor domains. LECT1 is thought to be involved in the regulation of proteolysis in skin barrier formation and immunity and this protein is highly expressed in thymus and mucous epithelia [22].…”
Section: Discussionmentioning
confidence: 99%
“…Low dose oral corticosteroids, etretinate and psoralen ultraviolet A therapy was also used. Topical tacrolimus will likely achieve minimal benefit, and may be contraindicated for patients with extensive skin involvement with concern for systemic absorption [22,31].…”
Section: Discussionmentioning
confidence: 99%